Harmonic Elimination of Seven Level Inverter with Switching Pattern Reconfiguration Technique Using Hybrid BBO/MAS Algorithm - R. Kavitha; Rani Thottungal; Brindha. R (Institute of Advanced Engineering and Science, 2016)
A hybrid optimization algorithm is proposed in this paper to find the optimum switching angles in a Cascaded Multilevel Inverter (CMLI). A seven level cascaded inverter is considered and optimum switching angles are found by hybrid Biogeographical Based Optimization search (BBO) / Mesh Adaptive Direct Search (MAS) algorithm. The fundamental frequency Selective Harmonic Elimination-Pulse Width Modulation (SHE-PWM) technique is applied in order to reduce the switching losses.Reconfiguration technique is also proposed to achieve harmonic elimination for entire Modulation index(M). The various performance indices like phase THD, line THD, lower order harmonics eliminated in a CMLI are calculated based on the optimized switching angles. A seven level CMLI is simulated in MATLAB/SIMULINK by using switching angles calculated from BBO/MAS algorithm and the FFT analysis of traditional SHE-PWM and reconfiguration SHE-PWM methods are compared and verified with the calculated values from BBO/MAS algorithm.